Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPAS - Ramdani, Riki; Maftuh, Ade; Nurani, Riga Zahara (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low learning outcomes of fourth-grade students in science learning, the use of learning models that are not yet appropriate to the material and students' lack of activity during learning. This study aims to determine the improvement in fourth-grade students' learning outcomes in science learning by implementing the project-based learning model. The type of research used is classroom action research with the Stephen Kemmis and Mc. Taggart model. Data collection techniques in this study were carried out through observation, tests, interviews, and documentation. Data analysis techniques in this study used qualitative and quantitative methods. The results of this study indicate that there was an increase in the percentage of student learning outcomes, which previously at the pre-cycle was 37.5%, then increased in cycle I to 62.5% and cycle II increased to 87.5%. It can be concluded that the application of the project-based learning model can improve the science learning outcomes of fourth-grade students at SDN Sukaati.